The PuReWidgets Toolkit for Interactive Public Display Applications - Cardoso, Jorge C. S. (2013)
In this paper we present PuReWidgets, a toolkit that supports multiple interaction mechanisms, asynchronous events, automatic web and mobile interface generation, and concurrent interaction. This is an early effort towards the creation of a programming toolkit that developers can incorporate into their public display applications to support the interaction process across multiple display systems without considering the specifics of what interaction modality will be used on each particular display.